2017
DOI: 10.1002/chem.201703221
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Containing Nitrite Reductase Employing Proton‐Coupled Spin‐Exchanged Electron‐Transfer and Multiproton Synchronized Transfer to Reduce Nitrite

Abstract: The possible catalytic mechanism of the reduction of nitrite by copper-containing nitrite reductases (CuNiRs) is examined by using the M06 function according to two copper models, which include type-one copper (T1Cu) and type-two copper (T2Cu) sites. Examinations confirm that the protonation of two residues, His255 and Asp98, near the T2Cu site, can modulate the redox states of T1Cu and T2Cu, but cannot directly cause electron transfer from T1Cu to T2Cu. The electron hole remains at the T2Cu site when only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 81 publications
3
13
1
Order By: Relevance
“…MSOX shows a side-on nitrosyl product bound to T2Cu as is observed in NO-soaked CuNIR crystals (15,18). However, several computational studies have suggested that direct release of NO without forming nitrosyl copper species is energetically favorable and hydroxyl T2Cu remains as a stable product (29)(30)(31)(32). The calculated activation energy shows good agreement with an activation energy value determined experimentally.…”
supporting
confidence: 68%
“…MSOX shows a side-on nitrosyl product bound to T2Cu as is observed in NO-soaked CuNIR crystals (15,18). However, several computational studies have suggested that direct release of NO without forming nitrosyl copper species is energetically favorable and hydroxyl T2Cu remains as a stable product (29)(30)(31)(32). The calculated activation energy shows good agreement with an activation energy value determined experimentally.…”
supporting
confidence: 68%
“…The TsNirK crystal structure also shows additional residues postulated to be relevant for catalysis in two-domain NirKs, with Gln239 and Thr240 [ Fig. 2(d)] catalytically equivalent to Glu279 and Thr280 in AfNir (Boulanger et al, 2000;Fukuda et al, 2016) and in AcNir (Qin et al, 2017). There is a hydrogen bond between His80 and the side chain of Gln239.…”
Section: Discussionmentioning
confidence: 95%
“…These results indicate that ET from T1Cu to T2Cu occurs after the T2Cu site receives the first proton and before obtains the second proton from the surroundings, which implies that the PT from Asp98 to the nitrite substrate are not the direct driving force for the inter-Cu ET. [26] Therefore, we infer that the proton conveying along the proton channel occurs from the surface of protein, which is far away from Asp98 or His255, essentially triggers the inter-Cu ET. The long-range PT pathway includes several PT steps, however, which step actually induces ET from T1Cu to T2Cu is unknown.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, the computational model containing T1Cu, T2Cu, all residues and H 2 O molecules as mentioned above, named EÀ W E3 À D, was constructed to explore the possible PT steps along the high-pH channel (Figure 1). The structure of EÀ W E3 À D not only contains all the residues of our previous models, [26] but also includes the relative residues constructing the high-PH channel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation